1980
DOI: 10.1002/jmv.1890050307
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus serotypes by serum neutralisation

Abstract: A neutralisation test using cell culture and indirect immunofluorescence was applied to isolates of rotavirus from 55 patients with gastroenteritis, in order to determine serotypes. Frequent cross-reactions were observed, but subsequent statistical analysis confirmed the existence of at least three distinct serotypes. Some results, not sufficient for analysis, suggest that at least five serotypes probably exist. It is suggested that two or more viral polypeptides might be involved in neutralisation, one of whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
88
0

Year Published

1981
1981
1994
1994

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(90 citation statements)
references
References 9 publications
2
88
0
Order By: Relevance
“…Several subgroups Greenberg et al 1983) and serotypes (Beards et al 1980;Wyatt et al 1982) have been identified by complement fixation tests (Thouless et al 1977;Zissis & Lambert, 1978), ELISA techniques (Yolken et al 1978;Thouless, Beards & Flewett, 1982) and neutralization assays (Beards et al 1980;Wyatt et al 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Several subgroups Greenberg et al 1983) and serotypes (Beards et al 1980;Wyatt et al 1982) have been identified by complement fixation tests (Thouless et al 1977;Zissis & Lambert, 1978), ELISA techniques (Yolken et al 1978;Thouless, Beards & Flewett, 1982) and neutralization assays (Beards et al 1980;Wyatt et al 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on rotavirus have shown that there are several serotypes in human and avian rotaviruses discriminated by serum neutralization (SN) tests (2,5,11,13). Although considerable attention has been paid to proving the existence of rotaviral serotypes in other species (4), comparatively little is known about those of bovine rotaviruses.…”
mentioning
confidence: 99%
“…They suggest that there may be serotypes in bovine rotaviruses by the SN test, as in human and avian rotaviruses (2,5,11,13). It is another point of interest that even in the same herd suffering from diarrhea, the serum showed different neutralization patterns against the isolates.…”
mentioning
confidence: 99%
“…It showed a two-way cross-reaction with B R V E4046 and a one-way crossreaction with BRV B223. However, cross-neutralization of BRV V1005 with B223-specific rabbit serum was not observed with the corresponding guinea-pig serum and cross-neutralization of BRV B223 with the V1005- * As determined in the fluorescent focus neutralization test (Beards et al, 1980). t The neutralization titre of UK/7 was > 10000 against both BRV UK and BRV NCDV.…”
Section: Discussionmentioning
confidence: 97%
“…The injections were repeated 14 days later and the rabbits were bled by cardiac puncture 7 to 10 days after the second injection. Neutralization of fluorescent focus production in MA-104 cells was used, essentially as described by Beards et al (1980). Titres are expressed as the reciprocal of the serum dilution reducing fluorescent foci by 50%…”
Section: -9503 © 1990 Sgmmentioning
confidence: 99%